The implementation and usability of HIRAID, a structured approach to emergency nursing assessment. (March 2020) - Curtis, Kate; Munroe, Belinda; Van, Connie; Elphick, Tiana-Lee
Abstract: Background: Emergency nurses are responsible for the initial assessment, management and safety of critically ill patients. HIRAID, an evidence-informed emergency nursing assessment framework, is known to improve emergency nursing patient-assessment in the simulated environment however has not been evaluated in the clinical setting. Methods: A pre-post design was used to assess the usability and impact of HIRAID on emergency nurses self-efficacy in the emergency department (ED). Nursing and medical staff from three Australian EDs were surveyed. Descriptive and optimal pooled sample t-tests statistics were conducted. Results: One hundred and two emergency nurses completed the pre-intervention self-efficacy survey and 63 completed the post-intervention self-efficacy and satisfaction survey. Forty-two and 17 medical officers completed the pre- and post-intervention satisfaction surveys, respectively. Nursing staff self-efficacy levels were unchanged pre- and post-HIRAID implementation (Mean (SD): 8.8 (0.21) vs. 8.7 (0.20)) as was medical staff satisfaction (Mean (SD):7.5 (1.43) vs. 7.8 (1.07)), although there was a trend towards improved communication. Conclusion: The HIRAID structured approach to patient assessment is acceptable, feasible, practical and appropriate for use in the clinical environment. Further research will demonstrate the direct effects of HIRAID on clinical performance.